Literature Review: Klasifikasi Citra Medis Penyakit Pneumonia dengan Convolutional Neural Network - Noufal Maulana; Muhammad Fauzan Rusby Kholiq; Muhammad Dabit H. A.; Geraldo Sabila F. (CV. Multi Kreasi Media, 2024)
Pneumonia is a dangerous respiratory infection with a fairly high mortality rate, especially in countries with limited medical resources. Examination of chest X-ray images is usually the main method for diagnosing this disease, but the process can be time consuming and requires special expertise. In this study, the Convolutional Neural Network (CNN) method was applied to help classify chest X-ray images into